Improved metagenome binning and assembly using deep variational autoencoders - Nissen, Jakob Nybo; Johansen, Joachim; Allesøe, Rosa Lundbye; Sønderby, Casper Kaae; Armenteros, Jose Juan Almagro; Grønbech, Christopher Heje; Jensen, Lars Juhl; Nielsen, Henrik Bjørn; Petersen, Thomas Nordahl; Winther, Ole; Rasmussen, Simon (Nature biotechnology, 2021)
Despite recent advances in metagenomic binning, reconstruction of microbial species from metagenomics data remains challenging. Here we develop variational autoencoders for metagenomic binning (VAMB), a program that uses deep variational autoencoders to encode sequence coabundance and k -mer distribution information before clustering. We show that a variational autoencoder is able to integrate these two distinct data types without any previous knowledge of the datasets. VAMB outperforms existing state-of-the-art binners, reconstructing 29–98% and 45% more near-complete (NC) genomes on simulated and real data, respectively. Furthermore, VAMB is able to separate closely related strains up to 99.5% average nucleotide identity (ANI), and reconstructed 255 and 91 NC Bacteroides vulgatus and Bacteroides dorei sample-specific genomes as two distinct clusters from a dataset of 1,000 human gut microbiome samples. We use 2,606 NC bins from this dataset to show that species of the human gut microbiome have different geographical distribution patterns. VAMB can be run on standard hardware and is freely available at https://github.com/RasmussenLab/vamb . Metagenomics data are resolved into their constituent genomes using a new deep learning method.